2016
DOI: 10.1080/14789949.2016.1261174
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and early intervention in prison: improving outcomes and reducing prison returns

Abstract: This is a repository copy of Early detection and early intervention in prison : improving outcomes and reducing prison returns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The net benefit of screening with multiple cut‐offs which has sensitivity (75%) and specificity (71%) comparable to the best studied tools ranged from 7 to 13% over the range of thresholds for which it was the optimal strategy. However, as discussed in the introduction, observational studies have reported approximately 3 to 5% increases in uptake of treatment following screening (Evans et al, ; Pillai et al, ), and some of these increases may be through greater provision of services to those who do not require treatment (Martin et al, ). Given these gaps from potential to actual impacts of screening, results of our subgroup analyses warrant attention to better understand the limitations of screening as currently practiced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The net benefit of screening with multiple cut‐offs which has sensitivity (75%) and specificity (71%) comparable to the best studied tools ranged from 7 to 13% over the range of thresholds for which it was the optimal strategy. However, as discussed in the introduction, observational studies have reported approximately 3 to 5% increases in uptake of treatment following screening (Evans et al, ; Pillai et al, ), and some of these increases may be through greater provision of services to those who do not require treatment (Martin et al, ). Given these gaps from potential to actual impacts of screening, results of our subgroup analyses warrant attention to better understand the limitations of screening as currently practiced.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the intensity of follow‐up to a positive screen may vary depending on the priorities of the screening process. For example, screening may aim to identify sub‐threshold or prodromal symptoms to prevent onset of illness (Evans et al, ; van Zoonen et al, ). In this case, the follow‐up to screening will be lower intensity and entail less potential harm; thus, a larger number of false positives would be tolerable and the treatment threshold would be lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of mental disorder among prisoners has been reported across the world and is well established in the international literature (Fazel & Baillargeon, ). Specific concerns have also been investigated, including alcohol and substance misuse (Kissell et al, ; Singleton, Farrell, & Meltzer, ), self‐harm and self‐inflicted death among prisoners (Hawton, Linsell, Adeniji, Sariaslan, & Fazel, ), traumatic brain injury (Williams, Cordan, Mewse, Tonks, & Burgess, ), attention deficit hyperactivity disorder (Young et al, ), and ultra‐high psychosis risk (Evans et al, ). Meanwhile, the idea that health care screening must take place at prison reception has gained international approval (United Nations General Assembly, ).…”
Section: Resultsmentioning
confidence: 99%
“…In correctional facilities in England and Wales analogous systems have been implemented (Hopkin et al, 2017 ). Local adaptions to screening processes in-prison have shown to statistically significantly improve measures of depression, anxiety and psychological distress for people detained in prison at high-risk of psychosis (Evans et al, 2017 ) and be relatively inexpensive (Brown, Cullen, Kooyman, & Forrester, 2015 ).…”
Section: Discussionmentioning
confidence: 99%